Transformation of Linear Alkenyl N-Alkoxy Carbamates into Cyclic Bromo Carbonates - Shyam Sathyamoorthi; Steven P. Kelley (Chemistry)
We present a protocol for the facile conversion of linear alkenyl N-alkoxy carbamates into cyclic bromo carbonates. The reaction is operationally simple, uses widely available, inexpensive reagents, and requires no rigorous exclusion of air or moisture. A range of functional groups is compatible, and the reaction diastereoselectivities vary from good to excellent. The reactions are scalable, and the resultant carbonates can be further transformed.